Historia de gentibus septentrionalibus : Romæ 1555 = Description of the northern peoples : Rome 1555.: Romæ 1555 = Description of the northern peoples : Rome 1555. Volume 1 (2017) - Magnus, Archbishop of Uppsala, Olaus, 1490-1557
No abstract available